(3fSeGJ GdCSMGQ aj WHbGJ QhGI cJH Gdabg hGdBKGQs - (3EHQGgje Hf GdbGSe Hf GdeDjO HGddg eMeO Hf GdefUhQ HGddg GdbGSe Hf eMeO GdMSjfj GdTgGQj,J (B1143 (3g` s ((3eOjfI UfYGA s)
(3ChdgG (B:s
(3JHOC HGdWHbI GdKGdKI (B: (3JTJed Ydi ef Qhi cJH CeJfG Ydjge GdSdGe ef QCS GdNeS eFI Zdi efJgi cJH gPg GdWHbI s
(3BNQgG (B:s
(3hHfi GdefUhQ GdeOQSI GdefUhQjI GdSadi ddMfajI HETGQI Gdaabjg Jhai SfI CQHY hSJjf hSJeFI , hOaf HebHQg HGH SgGe HeOjfI RHjO HdZ GdeUfa Edi gfG s
(3HgG fXGe GdJYbjHIs
(3HChdgG ChQGb ajgG JQGLe hahGFOs
(3cJHJ HNW eged GdfbW cKjQkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs